Pengelolaan Produk Samping Budidaya Jamur Tiram menjadi Pupuk Organik di Desa Danda Jaya, Barito Kuala - Rabiatul Wahdah; Riza Adrianoor Saputra; Untung Santoso; Yulia Padma Sari; Siska Aulia; Jean Melver Nehemia (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Danda Jaya Village is one of the primary oyster mushroom producing areas in Barito Kuala Regency, South Kalimantan Province, but until now, the baglog waste from these cultivation activities has not been optimally managed, potentially leading to environmental pollution. This Community Service (PKM) activity aims to increase the knowledge and skills of oyster mushroom cultivators in processing baglog waste into organic fertilizer. The implementation method involved preparation, execution—consisting of lectures and practical fertilizer-making sessions—and evaluation using questionnaires. The activity was attended by 24 participants who are members of the oyster mushroom cultivation group. The practical sessions utilized oyster mushroom baglog waste (50 kg) as the primary material, mixed with cow manure, bran, agricultural lime, EM4, and molasses. Evaluation results showed a significant increase in participant knowledge; while technical procedural knowledge ranged from 0‒18.75% before the activity, it surged to 80‒100% after the training. Currently, 100% of the participants understand that baglog waste can be processed into compost, which is expected to be independently applied to their respective agricultural lands in Danda Jaya Village to support environmental sustainability.